Research to Convert the Compression Ignition Engine to the HCCI Engine Using E20 Petrol Fuel - Le, Minh Xuân; Duong, Việt Dũng; Nguyen, Thanh Tuấn (Journal of Technical Education Science, 2022)
This paper presents the research results on converting the original single-cylinder diesel engine into an HCCI engine using biofuel E20. The research team analyzed to come up with a solution to convert the fuel supply system from the fuel injector directly into the combustion chamber into the E20 fuel injector on the intake manifold, and at the same time, choose the solution. Change the engine’s compression ratio to suit the engine running on the HCCI principle and for future research. The experiment was conducted based on the change of compression ratio of the engine corresponding to the engine’s rotational speed from 1000 rpm to 1600 rpm. At the measured results, we can confirm that the HCCI engine, when Using E20 gasoline with a compression ratio of 14, is suitable for experimental conditions. This is also the basis for future studies.